Corticosteroids as inductors of ovulation in Astyanax altiparanae (Characiformes: Characidae) during artificial reproduction - Parreira, Walquiria da Silva Pedra (2015)
Stress can be defined as a condition in which the dynamic equilibrium of the body is disturbed and several studies have demonstrated the action of some corticosteroids modulating stress situations, such as reproduction. However, the role of corticosteroids in fish reproduction can be either positive or deleterious, depending on many variables. In the Astyanax genus, the same stress stimulus can successfully induce the reproduction in Astyanax altiparanae, but not in other species of the same genus. Therefore, the aim of this study was to analyze cortisol and progestogens plasma levels and receptor gene expression in the ovaries of A. altiparanae, a teleost species that successfully reproduce using crowding and water level drawdown as stimulus. Three experimental groups were considered: Stress (high stocking density and water level drawdown); human chorionic gonadotropin (hCG, a positive control); and Saline (a control group). Females were sampled at three different moments of the artificial reproduction experiment, initial, intermediary and at spawning. Indices of spawning performance as, fertilization rate, Gonadosomatic Index (GSI), as well as histological analysis of the ovaries were carried out. 17α-hydroxiprogesterone (17 OHP) and cortisol (CORT) levels were measured in plasma by ELISA. Additionally, the ovarian gene expression of CORT and 17 OHP receptors (CR and PR) were carried out by Real-time quantitative PCR. Females from Stress and hCG groups released a larger volume of eggs when compared with females from the Saline (Control) group. Females from Stress group presented a decrease in GSI and ovaries mass at spawning, and many post ovulatory follicles (POFs) were present in the ovaries after spawning. At the intermediary sampling, plasma levels of CORT increased in females from the Stress group, but not in the hCG and Saline groups. 17 OHP levels did not change during the experiment. PR gene was more expressed in females from hCG group throughout the experiment, but CR gene expression did not change. We suggest a possible role of CORT as an inducing agent in ovulation and/or spawning of A. altiparanae. CR and PR did not seem to be the candidates for triggering ovulation, so the relationship between the derivative of progesterone (17,20DHP) should be deeper studied, as well as the role of CORT and different progestagens in A. altiparanae reproduction